The Serial Mediation Effects of Social Support and Self-Efficacy on Health Literacy and Self-Management Behaviors Among Young and Middle-Aged Cardiac Patients After Percutaneous Coronary Intervention: A Cross-Sectional Study in China - Liu W; Qian S; Hu Y; Zhang R (Risk Management and Healthcare Policy)
Wenqin Liu,1 Shuyan Qian,1 Yihan Hu,2 Ruo Zhang3 1DSA Center, The Second Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang Province, People’s Republic of China; 2Wenzhou Medical University, Wenzhou, Zhejiang Province, People’s Republic of China; 3Nurse Practitioner, Nursing Department, The Second Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang Province, People’s Republic of ChinaCorrespondence: Ruo Zhang, Email zr2005zr@163.comBackground: Coronary heart disease (CHD) is a significant public health concern affecting an increasing number of young and middle-aged adults. Effective self-management is essential to promote the recovery and quality of life of patients with CHD after percutaneous coronary intervention (PCI), and is closely related to health literacy. However, little is known about the underlying mechanisms of this association.Objective: This study aimed to investigate the mediating effects of social support and self-efficacy in the relationship between health literacy and self-management behaviors among young and middle-aged patients with CHD after PCI.Methods: A cross-sectional study was conducted among 360 CHD patients aged 18– 59 who after PCI within 1 to 3 months. The data were collected from September 2022 to July 2023 in a tertiary hospital in China. The questionnaires were utilized to gather data on demographic characteristics, social support, self-efficacy, health literacy, and self-management behaviors. The serial mediation model was examined via bootstrapping techniques using SPSS PROCESS v.4.3 macros (Model 6).Results: Participants health literacy was associated with self-management behaviors both directly (β=0.334, P< 0.001) and indirectly through social support (β=0.149, P< 0.001) and self-efficacy (β=0.095, P< 0.001). Social support and self-efficacy serially mediated the association between health literacy and self-management behaviors (β=0.226, P< 0.001), with the total indirect effects accounting for 44.3%, these three mediating paths account for 24.8%, 15.8%, and 3.7% of the overall effect, respectively.Conclusion: Health literacy influences self-management behaviors that the study’s findings suggest were significant. Social support and self-efficacy act as mediators in the relationship between health literacy and self-management behaviors. Our findings provide helpful guidance for the future development of targeted and effective psychosocial interventions to enhance CHD patients’ self-management, ultimately improving prognosis and quality of life.Keywords: young and middle-age, health literacy, self-management behaviors, social support, self-efficacy, serial mediation